Spatio-temporal properties of oculomotor activation by multiple, simultaneous peripheral stimuli. (November 2021) - Christie, John; Hilchey, Matthew D.; Klein, Raymond M.
Abstract: Oculomotor research shows that eye movements are primed toward the midpoint of an array of visual stimuli, such that an eye movement to a visual target is executed most rapidly when it appears near the midpoint of an earlier array. At longer intervals between the prime and target, this facilitatory effect can reverse to become inhibitory — such that eye movements are slower when made toward the midpoint – but the source of this inhibition is unclear. One of our prior studies suggests a global source: target proximity to the midpoint determines inhibition, consistent with the notion that oculomotor activation is responsible for the effect and the original definition of inhibition of return. A later study suggests a local source: target proximity to the nearest array element determines inhibition, consistent with the notion that repeat stimulation of an input pathway is responsible. To resolve the ambiguity we systematically test whether timing differences between studies altered the source of the inhibition. We find that both previously observed patterns are reproducible depending on the prime offset – target onset asynchrony. We also resolve the discrepancy by showing that when this asynchrony is less than 200 ms, target proximity to the array's midpoint and its proximity to any given array element can jointly determine inhibition, whereas when the asynchrony is approximately 200 ms, inhibition is robust at the midpoint of the array. At longer asynchronies, all inhibitory effects rapidly dissipate.